Work-Life Balance And Its Significant Positive Effect On Employee Performance: Evidence From BNN Maluku Province - Sulaiman Wasahua; Indra Wahyudi; Agung K. Henaulu; Edi Arijanto Soselisa; Efendy Rumakat (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to examine the impact of work-life balance on the performance of employees at the National Narcotics Board (Badan Narkotika Nasional/BNN) of Maluku Province. The growing demands on law enforcement personnel necessitate an understanding of how equilibrium between professional duties and personal life affects workplace outcomes. This explanatory research employed a quantitative approach with a census sampling technique, utilizing the entire population of 57 employees as respondents. Primary data were collected through questionnaires measured by a Likert scale, and the analysis included validity and reliability tests, simple linear regression, and coefficient of determination The findings reveal that work-life balance has a significant positive influence on employee performance, as indicated by a significance value of 0.000 (< 0.05). The regression equation Y = 6.649 + 0.539X demonstrates that for every unit increase in work-life balance, employee performance increases by 0.539. Furthermore, work-life balance explains 60.5% of the variance in employee performance (R² = 0.605), while the remaining 39.5% is influenced by other variables not examined in this study. It is concluded that enhancing work-life balance through supportive policies, such as flexible working arrangements and wellness programs, can substantially improve employee effectiveness. Future research is encouraged to explore additional factors like motivation and compensation to provide a more comprehensive understanding of performance determinants in public sector organizations.